Successful achievement after heterotopic transplantations of long-term stored ovarian tissue in Hodgkin's lymphoma survivor. (3rd June 2019) - Fabbri, R.; Seracchioli, R.; Vicenti, R.; Paradisi, R.; Rossi, S.; De Meis, L.; Ciccarone, M.; Caprara, G.; Martino, N. A.; Macciocca, M.
Abstract: In this case report, we describe the outcomes of two heterotopic transplantations of cryopreserved ovarian tissue performed in a patient with HL, after 11 and 15 years of storage. At the age of 30, the patient underwent laparoscopy to collect ovarian tissue for cryopreservation before chemotherapy and radiotherapy. Eleven years later she experienced premature ovarian failure (POF). As the patient was only interested in endocrine function recovery, two heterotopic ovarian tissue transplantations were performed in the abdominal wall above the rectus muscle respectively 11 and 15 years after cryopreservation. Before transplantation, ovarian samples were analyzed to assess neoplastic contamination and tissue quality. The analysis on thawed ovarian tissue did not reveal micrometastasis and it showed well-preserved follicles and stroma. After both ovarian tissue grafting, menopausal symptoms ceased. The patient had periods approximately every 30-days and hormonal levels were within the premenopausal range. The endocrine function lasted 3-years after the first heterotopic transplantation and is still ongoing after second transplantation. Cryopreservation of ovarian tissue should be proposed to HL patients, as the incidence of POF as a long-term complication is not negligible. In these patients heterotopic transplantation is a useful tool to eliminate menopausal symptoms, preventing osteoporosis and reducing cardiovascular risks.